Di Antara Iman dan Cinta: Eksplorasi Pernikahan Beda Agama dalam Perspektif Filsafat, Agama, dan Hukum - Siti Faridah; Darojat Darojat (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This article explores the phenomenon of interfaith marriages in Indonesia from the perspectives of philosophy, religion and law, with the aim of providing a comprehensive understanding of the dynamics that occur. In the context of a religiously diverse society, interfaith marriage is often a topic of public discussion. Modernization, globalization and increased awareness of human rights have encouraged the younger generation to be more open to interfaith marriages, even though they still face legal challenges and social stigma. Qualitative research methods were used to explore the experiences and views of interfaith couples through in-depth interviews, participant observation and official documentation. The research results show that interfaith couples must navigate various challenges from family, society, and legal aspects, but can maintain harmonious relationships through open dialogue and mutual respect for each other's beliefs. The respondents in this study were three couples in interfaith marriages who provided a real picture of the dynamics of interfaith marriages in Indonesia. These findings emphasize the importance of revising the law to better accommodate religious diversity and support harmonious relations amidst differences.